2011
DOI: 10.1016/j.aorn.2010.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Using Nurse‐to‐Patient Telephone Calls to Reduce Day‐of‐Surgery Cancellations

Abstract: Day-of-surgery cancellations are costly and frustrating for both the patient and the health care team. This is especially true in ambulatory surgical centers where it can be difficult to schedule a replacement procedure on short notice. Preoperative nurses at the University of North Carolina Health Care ambulatory surgical center were able to decrease the daily cancellation rate by 53%, increase patient satisfaction scores, and increase OR use by targeting three main reasons for cancellations during a preopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 3 publications
1
25
2
2
Order By: Relevance
“…Previous studies have reported a significant decrease in total DOS cancellation rates after implementing preoperative interventions or remodelling preoperative care processes. However, the results are not easily comparable to ours, as the definitions for DOS cancellations vary between studies (Boudreau & Gibson, ; Deng et al., ; Haufler & Harrington, ; Hovlid et al., ; McKendrick et al., ; Ming Teh et al., ; Muckler et al., ; Sebach et al., ) and for example the three category classification (patient, physician, hospital) presented by Tung, Dexter, Jakubczyk, and Glick () would have given too limited information for our study purposes (Dexter et al., ; Tung et al., ). Other studies are also based on limited patient groups (Boudreau & Gibson, ; Deng et al., ; Higson & Finlay, ) or were conducted in substantially smaller hospitals than in this study (Haufler & Harrington, ; Hovlid et al., ; McKendrick et al., ; Ming Teh et al., ; Muckler et al., ; Sebach et al., ; Siragusa et al., ).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Previous studies have reported a significant decrease in total DOS cancellation rates after implementing preoperative interventions or remodelling preoperative care processes. However, the results are not easily comparable to ours, as the definitions for DOS cancellations vary between studies (Boudreau & Gibson, ; Deng et al., ; Haufler & Harrington, ; Hovlid et al., ; McKendrick et al., ; Ming Teh et al., ; Muckler et al., ; Sebach et al., ) and for example the three category classification (patient, physician, hospital) presented by Tung, Dexter, Jakubczyk, and Glick () would have given too limited information for our study purposes (Dexter et al., ; Tung et al., ). Other studies are also based on limited patient groups (Boudreau & Gibson, ; Deng et al., ; Higson & Finlay, ) or were conducted in substantially smaller hospitals than in this study (Haufler & Harrington, ; Hovlid et al., ; McKendrick et al., ; Ming Teh et al., ; Muckler et al., ; Sebach et al., ; Siragusa et al., ).…”
Section: Discussioncontrasting
confidence: 57%
“…It has been stated that the success of a preoperative process can be well monitored by last‐minute cancellations (Verma et al., ). Several comparative studies presented positive outcomes of interventions carried out in the preoperative process to reduce cancellations (Bathala et al., ; Boudreau & Gibson, ; Deng et al., ; Gheysari et al., ; Haufler & Harrington, ; Hovlid et al., ; McKendrick et al., ; Ming Teh et al., ; Muckler et al., ; Sebach et al., ; Siragusa et al., ) (Table ). To the best of our knowledge, this is the first study to evaluate the impact of implementing an evidence‐based and structured preoperative protocol in a university hospital with all operative specialties included while also searching for meaningful factors in organising preoperative care to reduce day of cancellations.…”
Section: Introductionmentioning
confidence: 99%
“…According to the "Funding Regulation on the New Cooperative Medical Scheme" published by the Ministry of Finance and Ministry of Health [28], surplus funds at the end of the year should not exceed 15% of revenue, and the cumulative surplus should be remain less than 25%. During the initial phases of implementation, many NCMS management teams were concerned about exhausting annual revenues and worked vigorously to build reserves.…”
Section: Discussionmentioning
confidence: 99%
“…Recognising that maximum efficacy of day surgery units requires the minimization of patient non-attendances, many initiatives have been described including postal questionnaires [24] , telephone call screening [25] and telephone reminders.…”
Section: Discussionmentioning
confidence: 99%